2018
DOI: 10.1158/0008-5472.can-18-0618
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A Availability during DNA Replication Stress Is a Major Determinant of Cisplatin Resistance in Ovarian Cancer Cells

Abstract: Intrinsic and acquired resistance to cisplatin remains a primary hurdle to treatment of high-grade serous ovarian cancer (HGSOC). Cisplatin selectively kills tumor cells by inducing DNA crosslinks that block replicative DNA polymerases. Single-stranded DNA (ssDNA) generated at resulting stalled replication forks (RF) is bound and protected by heterotrimeric replication protein A (RPA), which then serves as a platform for recruitment and activation of replication stress response factors. Cells deficient in this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 51 publications
4
58
0
1
Order By: Relevance
“…Hierarchical bi‐clustering analysis indicated significant gene signatures in TRIB2 High /MAP3K1High GBM compared withTRIB2 Low /MAP3K1Low GBM (Figure A). Additionally, KEGG pathway analysis demonstrated multiple molecular pathways that were related to malignant cancer and therapeutic resistance, including cell cycle pathways and the NOTCH, DNA replication, and p53 pathways. Similar results were observed by gene set enrichment analysis (GSEA) (Figure C,D, and E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchical bi‐clustering analysis indicated significant gene signatures in TRIB2 High /MAP3K1High GBM compared withTRIB2 Low /MAP3K1Low GBM (Figure A). Additionally, KEGG pathway analysis demonstrated multiple molecular pathways that were related to malignant cancer and therapeutic resistance, including cell cycle pathways and the NOTCH, DNA replication, and p53 pathways. Similar results were observed by gene set enrichment analysis (GSEA) (Figure C,D, and E).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence has suggested that rapid acquired therapeutic resistance is the major cause of the failure of standard comprehensive treatments, leading to the recurrence and high mortality of glioma . Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma . Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…replication stress is demonstrated to be a vital determinant of cisplatin resistance in HGSOC cells (52). We demonstrate that RPA mediates RING1A localization to damage sites connecting NER and HRR pathways to RING1A mediated gH2AXub1 (Supplementary Figure S6C).…”
Section: Exhaustion Of Rpa (A Common Player In Both Gg-ner and Hrr) Dmentioning
confidence: 62%
“…Bélanger et al (2018) reported that RPA exhaustion represents a major determinant of cisplatin sensitivity in ovarian cancer cell lines, a finding that harbors an important implication toward improving therapy of various cancers that initially respond to platinum-based agents but later relapse due to intrinsic or acquired drug resistance [26]. Wang et al (2018) showed that RPA70 promotes tumor proliferation via CDK4/Cyclin-D pathway [27].…”
Section: Discussionmentioning
confidence: 99%